Intragastric nitrites, nitrosamines, and bacterial overgrowth during cimetidine treatment. Issue 12 (December 1982) - Stockbrugger, R W; Cotton, P B; Eugenides, N; Bartholomew, B A; Hill, M J; Walters, C L
Abstract : A six week course of cimetidine (1 g/day) healed peptic ulcers in 20 of 23 patients (14 with duodenal ulcer, nine with gastric ulcer). Reduction of basal acid output by 73% and peak acid output by 36% led to a rise in concentrations of intragastric aerobic bacteria and nitrate-reducing bacteria. While the mean intragastric concentration of nitrate was unchanged by treatment, there were statistically significant rises in nitrite and N-nitrosamine concentrations. The conversion from nitrates to nitrites was closely related to the occurrence of nitrate-reducing bacteria. In three patients the intragastric milieu had returned to normal two months after cimetidine treatment had been discontinued. Mean nitrite and N-nitrosamine concentrations did not return to pre-treatment levels in the group of eight patients who remained on maintenance cimetidine (0.4 g at night-time) for three months after the full dose treatment. This study shows that cimetidine treatment can create an intragastric milieu resembling that of atrophic gastritis. Large scale and long-term studies are necessary to establish whether these findings have any clinical significance.